The influence of pedagogical reflection on design educational and professional plans of future teachers. - M. A. Golovchin (Высшее образование в России)
The article analyzes the level of formation of pedagogical reflection among graduates studying the pedagogical specialties, and also generalizes the nature of the influence of pedagogical reflection on the educational and professional plans of future teachers after receiving a diploma. In the study, the author considers pedagogical reflection as a prestart state of a specialist, embodied in meta-competence, which allows one to assess one’s professional knowledge and skills as sufficient or insufficient to work in the acquired specialty.As  a  part  of  the  study,  a  vision  of  the  nature  and  structure  of  the  phenomenon  of  pedagogical reflection founded on a competency-based approach was formed. The algorithm was proposed for assessing the level of formation of pedagogical reflection among graduates based on the use of factor analysis.  The  algorithm  was  tested  on  data  from  a  questionnaire  survey  conducted  in  2023  by  the Voluntary Research Center of the Russian Academy of Sciences (RAS) among graduates studying to become teachers in the Vologda region. As a result of testing, it was revealed that after receiving a diploma, graduates with critical reflection more often than others want to connect their lives with work at school and see the future of their children in the teaching profession. Graduates with moderate  and  weak  reflection  are  less  likely  to  design  appropriate  plans.  In  the  course  of  further generalization,  a  procedural  model  of  the  influence  of  pedagogical  reflection  on  the  professional development of a university graduate was developed.The scientific novelty of the study lies in the new perspective of posing the question of pedagogical reflection as a factor in educational and professional choice; the author’s methodology for summarizing the  level  of  formation of  professional  reflection  within  the framework  of  factor analysis; a conceptual model that describes the influence of reflection on the professional development of a graduate, focusing on “soft” mechanisms that can be used to solve personnel problems in the education system. The article proposes a set of approaches to solving the problems of training reflective teachers, which can be introduced into management practice.